NATURE SOUNDS MUSIC TO DECREASED ANXIETY ON CRITICALLY ILL PATIENTS - KURNIA WIJAYANTI (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2016)
Nature sound music is a combination between classical music with sounds of nature. The use of natural sound music like the sounds of birds, waves, wind, and water flow as a medical therapy has achieved satisfactory results that can improve relaxation, physical condition, and psychological state for individuals of various ages. This study aimed to determine the effect of natural sound music to decreased anxiety on critically ill patients in the ICU. This research is helpful in healing the critical patient, and as the basis for realizing evidence based practice in the management of critically ill patients.This research is using quasi-experimental non-equivalent to the pre-posttest control group design, with consecutive sampling by randomized allocation. Respondents were 20 people the intervention group and 18 people in the control group. Nature sounds music that was used is the sound of birds with a combination of 2 x 30 minutes in the morning (08.00-noon) and in the evening (20:00 to 22:00) for 3 days. Anxiety levels were measured using visual analog scale-anxiety (VAS-A). Data then were analyzed using Wilcoxon and Mann Whitney.The results of this study showed a decrease in anxiety in the intervention group with a value of 62.25 ± 7.304 pretest, posttest 41.65 ± 5.976, whereas the control group pretest 46.55 ± 12.76, 43.00 ± 12.35 posttest. The result of the comparison test on the anxiety before and after intervention in the intervention group p = 0.000 (p <0.05) and in the control group p = 0.007 (p <0.05). While the results of the difference test on the anxiety between the intervention group and the control group were p = 0.000 (p <0.05), which means there is a significant difference in anxiety levels between the intervention group and control group. Conclusion. Music sounds of nature is effective to reduce anxiety in critically ill patients.Keywords: music therapy, natural sounds, anxiety.